2013
DOI: 10.1007/s00345-013-1023-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic study between human normal motility sperm and idiopathic asthenozoospermia

Abstract: These experimental results expand the scope of the protein database, generating targets for further investigation of the pathogenic mechanism of idiopathic asthenozoospermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 29 publications
2
54
0
3
Order By: Relevance
“…The function and exact location of this protein in flagella has not yet been clarified. Shen et al (2013) showed lower amounts of this protein in idiopathic asthenoospermia [47]. Paasch et al (2011) demonstrated higher expression levels of SPANX C, a isomer form of protein, in the sperm of diabetic and obese individuals [48].…”
Section: Discussionmentioning
confidence: 94%
“…The function and exact location of this protein in flagella has not yet been clarified. Shen et al (2013) showed lower amounts of this protein in idiopathic asthenoospermia [47]. Paasch et al (2011) demonstrated higher expression levels of SPANX C, a isomer form of protein, in the sperm of diabetic and obese individuals [48].…”
Section: Discussionmentioning
confidence: 94%
“…In the algorithm, we initialize the map with a size of (26,5) and the training is done in two phases: (a) rough training with large (initial) neighborhood radius and large (initial) learning rate; (b) fine-tuning with small radius and learning rate. The batch training algorithm is iterative, but instead of using a single data vector at a time, the whole data set is presented to the map before any adjustments are made.…”
Section: Validation Of Pathways By Clustering Proteins By Self Organimentioning
confidence: 99%
“…Similarly, a study in which obesity-induced asthenozoospermic sperm was analyzed reported alterations in the expression of proteins involved in cytoskeletal regulation, vesicle biogenesis, metabolism and protein degradation involved in spermiogenesis and sperm motility [95]. Interestingly, another comparative study of sperm proteome of asthenozoospermic phenotype with its transcriptome revealed that the effect on sperm motility is not entirely consistent at different molecular levels and evidenced that PTMs, such as N-glycosylation, may play an important role in sperm motility [96]. Phosphorylation is another important PTM that regulates sperm motility that has also been subject for differential proteomic studies.…”
Section: Studymentioning
confidence: 94%